Metabolic Instability of Cyanothiazolidine‐Based Prolyl Oligopeptidase Inhibitors: a Structural Assignment Challenge and Potential Medicinal Chemistry Implications. Issue 7 (28th May 2015) - Schiavini, Paolo; Pottel, Joshua; Moitessier, Nicolas; Auclair, Karine
Abstract As part of the development of cyanothiazolidine‐based prolyl oligopeptidase inhibitors, initial metabolism studies suggested multiple sites of oxidation by P450 enzymes. Surprisingly, in‐depth investigations revealed that epimerization at multiple stereogenic centers was responsible for the conversion of the single primary metabolite into a panel of secondary metabolites. The rapid isomerization of all seven detected molecules precluded the use of NMR spectroscopy or X‐ray crystallography for complete structural determination, presenting an interesting structure elucidation challenge. Through a combination of LC–MS analysis, synthetic work, deuterium exchange studies, and computational predictions, we were able to characterize all metabolites and to elucidate their dynamic behavior in solution. In the context of drug development, this study reveals that cyanothiazolidine moieties are problematic due to their rapid P450‐mediated oxidation and the unpredictable stability of the corresponding metabolites.